2020
DOI: 10.1556/2006.2020.00053
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic lockdown and problematic eating behaviors in a student population

Abstract: Background and aimsSince mid-March 2020, over 3 billion people have been confined as a result of the COVID-19 pandemic. Problematic eating behaviors are likely to be impacted by the pandemic through multiple pathways. This study examined the relationships between stress related to lockdown measures and binge eating and dietary restriction in a population of French students during the first week of confinement.MethodsA sample of undergraduate students (N = 5,738) completed an online questionnaire 7 days after l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
156
6
14

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(188 citation statements)
references
References 30 publications
12
156
6
14
Order By: Relevance
“…Participants living by themselves, as well as participants reporting more than one stressful life event (e.g bereavement) were more likely to fall into this group. Notably, lockdown measures have been linked to disordered eating behaviors commonly seen in eating disorders, such increased restriction of food intake and binge eating behaviors [32]. Further, patients with eating disorders have described lockdown as detrimental, reporting disruption of routines and decreased feelings of control which increased worries about their illness [33].…”
Section: Discussionmentioning
confidence: 99%
“…Participants living by themselves, as well as participants reporting more than one stressful life event (e.g bereavement) were more likely to fall into this group. Notably, lockdown measures have been linked to disordered eating behaviors commonly seen in eating disorders, such increased restriction of food intake and binge eating behaviors [32]. Further, patients with eating disorders have described lockdown as detrimental, reporting disruption of routines and decreased feelings of control which increased worries about their illness [33].…”
Section: Discussionmentioning
confidence: 99%
“…Previously published evidence also suggests emotional over-eating and emotional under-eating are responses to anxiety [40]. Effects of anxiety on maladaptive appetitive traits may be even more pronounced due to the additional stress and worry of the COVID-19 pandemic [2,9,23,41]. Moreover, there may be a bi-directional relationship between anxiety and appetitive traits.…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, stressful life events were positively associated with extreme weight control behaviors and binge eating (Loth et al, 2008), which have been identi ed as signi cant precursors of eating disorder onset, maintenance, and relapse (Degortes et al, 2014;Grilo et al, 2012). Moreover, stress was associated with a greater likelihood of binge eating and dietary restriction during the COVID-19 epidemic (Flaudias, 2020). A previous study showed that the perceived severity of COVID-19 was associated with less perceived controllability (Li et al, 2020), which may trigger a sense of stress (Lazarus, 2006).…”
Section: Perceived Severity Of Covid-19 Stress and Eating Problemsmentioning
confidence: 99%
“…Home con nement could be a catalyst for disordered eating behaviors (Brown et al, 2021). For instance, in a sample of 5738 French undergraduate students, home con nement was associated with more binge eating and dietary restriction (Flaudias, 2020). During the COVID-19 lockdown, the sense of hunger and satiety changed for more than half of the population, in the manner of less/increased appetite and eating more than usual (Di Renzo et al, 2020;Kriaucioniene et al, 2020;Owen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation